BtoxDB: a comprehensive database of protein structural data on toxin-antitoxin systems - Bertucci Barbosa, Luiz Carlos; Garrido, Saulo Santesso [UNESP]; Marchetto, Reinaldo [UNESP] (Elsevier B.V., 2015)
Purpose: Toxin-antitoxin (TA) systems are diverse and abundant genetic modules in prokaryotic cells that are typically formed by two genes encoding a stable toxin and a labile antitoxin. Because TA systems are able to repress growth or kill cells and are considered to be important actors in cell persistence (multidrug resistance without genetic change), these modules are considered potential targets for alternative drug design. In this scenario, structural information for the proteins in these systems is highly valuable. In this report, we describe the development of a web-based system, named BtoxDB, that stores all protein structural data on TA systems.Methods: The BtoxDB database was implemented as a MySQL relational database using PHP scripting language. Web interfaces were developed using HTML, CSS and JavaScript. The data were collected from the PDB, UniProt and Entrez databases. These data were appropriately filtered using specialized literature and our previous knowledge about toxin-antitoxin systems.Results: The database provides three modules ("Search", "Browse" and "Statistics") that enable searches, acquisition of contents and access to statistical data. Direct links to matching external databases are also available.Conclusions: The compilation of all protein structural data on TA systems in one platform is highly useful for researchers interested in this content. BtoxDB is publicly available at http://www.gurupi.uftedu.br/ btoxdb. (C) 2015 Elsevier Ltd. All rights reserved.
Keywords: Toxin-antitoxin (TA) systems; Structural database; Persistence; Alternative antimicrobials; Drug targets